Mastering your Fellowship - Mergan Naidoo; Klaus B. von Pressentin; Tasleem Ras; Michele Torlutter (South African Family Practice)
The series, “Mastering your Fellowship”, provides examples of the question format encountered in the FCFP(SA) examination. The series aims to help family medicine registrars and their supervisors prepare for this examination. Model answers are available online.